TECHNOLOGY OF DEEP SOIL LOOSENING ON SMALL HOMESTEAD LANDS - Ляшенко, С. В. (Scientific Progress & Innovations, 2015)
The known scientific researches confirmed the necessity of destruction close-settled soils. Existent agrotechnical technologies of treatment soil are inapplicable for the terms of subsidiary areas. Technical solution problems is offered by the use fuel-efficient power machines. The recommended chart is resulted for implementation of technological process of the deep loosening of soil on subsidiary areas. Technical solution is offered – deep loosening of soil for diminishing of influencing of subsurface layer of soil which appears on the small holdings as a result of permanent reiteration of methods of his till on physico-mechanical properties of soil and productivity of agricultural cultures.